Database Design / Second Edition - Wiederhold Gio (Mcgraw Hill Book Company, 1983)
Preface, Definitions and Introduction, Hardware and Its Parameters, File Structures and Design, Basic File System Organization, Hybrid File Organizations, Overall File System Evaluation, Techniques, Database Structure, Schemas, Database Implementation, Query Languages, Security and Operation, Methods to Gain Reliability, Protection of Privacy, Integrity of Databases, Coding, Data Base Operation and Management, Index for Alternative Terminology, List of Database Systems, Symblos Used, Bibliography, Index.